UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BUAH SENGGANI (Melastoma malabathricum L.) METODE DPPH (2,2-Diphenyl-1- picrylhidrazyl) SERTA APLIKASINYA PADA KRIM ANTIOKSIDAN - Dian Kartikasari; Hairunisa; Meri Ropiqa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
The ripe senggani fruit is purple, which indicates the high content of antioxidants in it. Antioxidants are used to protect the skin from oxidative damage so as to prevent premature aging. In cream preparations, a part that plays a role in determining the physical properties and stability of the cream is the emulsifier. Tween 80 and span 80 are emulgators that are often used simultaneously. This study aims to find out the antioxidant activity of extract of senggani fruit by looking at IC50 value was done by DPPH reaction method (2,2-Diphenyl-1-picrylhidrazyl) and formulate it into cream preparation with comparison concentration of tween 80 and span 80 then do the evaluation of physical properties of cream. The extracts were formulated in cream dosage form and then evaluated the physical properties includes organoleptis test, homogenity, dispersion, cream type, pH, and viscosity. IC50 value obtained is 52.032 ppm. The result of evaluation of physical properties of cream yielding good preparation is formula 3 with concentration of tween 80 is 8% and span 80 is 4%.